2000
DOI: 10.1080/09669580008667374
|View full text |Cite
|
Sign up to set email alerts
|

'Staying Within the Fence': Lifestyle Entrepreneurship in Tourism

Abstract: Lifestyle, non-economic motives have been recognised as significant stimuli for tourism entrepreneurship and growth of the small-business sector. Tourism research, to date, has focused on the conceptualisation of entrepreneurship informed largely by economic analysis. In this context, the long-term survival of lifestyle entrepreneurs in tourism has been addressed as a constraint within regional economic development. Our research of an emerging cohort of lifestyle entrepreneurs in New Zealand tourism, focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
454
1
21

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(505 citation statements)
references
References 19 publications
29
454
1
21
Order By: Relevance
“…The European Commission's drive over the past decade or more to reduce the 'burden' of regulation, for example, is predicated on the notion that to do so will release enterprise, ie firms that would otherwise be dynamically creating new jobs, which are somehow held back by the regulatory framework. In practice, lifestyle motivations predominate in the tourism sector (Ateljevic and Doorne, 2000;Getz and Carlsen, 2005).…”
Section: Conceptualizing the Small Firm In Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…The European Commission's drive over the past decade or more to reduce the 'burden' of regulation, for example, is predicated on the notion that to do so will release enterprise, ie firms that would otherwise be dynamically creating new jobs, which are somehow held back by the regulatory framework. In practice, lifestyle motivations predominate in the tourism sector (Ateljevic and Doorne, 2000;Getz and Carlsen, 2005).…”
Section: Conceptualizing the Small Firm In Tourismmentioning
confidence: 99%
“…The precise characterization of 'success' for these firms was, then, grounded in their own circumstances. Ateljevic and Doorne's (2000) work drew attention to the potential role of values in conditioning business practices for some owners, and found empirical evidence of operators working in niche markets, but with a strong sense of community and a concern for the environment. More recently, it has been suggested that 'lifestyle entrepreneurship' might also encompass a desire to generate a 'good' standard of living, operate a professionally organized business, but within a particular lifestyle or cultural 'framework'.…”
Section: Conceptualizing the Small Firm In Tourismmentioning
confidence: 99%
“…The diversification potential is often restricted by the entrepreneurs' inability to capitalise on opportunities [101]. Tourism is often located in attractive regions with concentrations of lifestyle entrepreneurs, whose non-growth orientation and non-economic motivation constrain the development of tourism destinations [102,103]. They tend to resist change, fear of technology and bureaucracy, and are characterized by traditional thinking, lethargy, short termism and being risk averse [104].…”
Section: Entrepreneurial Discoverymentioning
confidence: 99%
“…In the same vein, Ateljevic and Doorne (2000) argue that small-scale tourism businesses are becoming more important due to the demand of a new hybrid of tourists. The advent of this lifestyle entrepreneur has been a positive stimulus in the growth of small tourism related businesses or tourism entrepreneurship.…”
Section: Alternative Developmentmentioning
confidence: 99%